Study Of The Number Of Traded Shares Effect On Damascus Stock Exchange Index Return Using Co-Integration. - أحمد طالب; محسن حسن عبير (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Given that investing in securities is an investment with a return and a risk at the same time, the investor is interested in determining the expected return on investment in a particular project or security to make the optimum investment decision. This return is related to many factors affecting its amount or its achievement, some of these factors are related to the economy in total, and some of them are related to the company or the investment project itself. Since the trading volume measured by the number of traded shares is an important indicator of market liquidity and the company’s performance, as it can be taken into account when making the investment decision, so we are going to study these variables and know its effect on stock return in Damascus Stock Exchange. This research aims to study the effect of the trading volume measured by the number of traded shares on the return of the Damascus Stock Exchange index using Co- Integration Test using E-Views 9 program for the period from 2010 to 2018, and also aims to know if there is a long run equilibration relationship between them. The research has found that there is a fluctuation in the return value of the index and the trading volume value measured by the number of traded shares, and the trading volume measured by the number of traded shares and return of the index are integrated and there is a long run equilibration relationship between them.